Social Constructionism: Reflecting Team Discussion Group Applied to Scientific Work - Donoso Niemeyer, Tania (Revista de Psicología, 2004)
The present article shows how a Reflecting Team Discussion Group can be used as a method in psychological qualitative scientific research. The theoretical postulates have their origin in Social Constructionism, from which it is possible to interpret the person’s meanings and cognitive attributions on certain topics or problems. Social Constructionism studies psychological phenomena by focusing on the way life history personal experiences, social context and theoretical knowledge on specific topics, are applied in the person’s present experience. The method used is illustrated by a Reflecting Team Discussion Group munexperience, which studied a group of 6 mothers with children from 5 to 8 years. The purpose was to explore the stories of their experiences and meaning attributions they signified as their main strengths and weakness in child rearing.